PHYSICAL ACTIVITIES PARTICIPATION AND ACADEMIC PERFORMANCE OF THE CASE STUDENTS OF COLEGIO DE LA PURISIMA CONCEPCION - Gorriceta, Gay Maricon G. (President University, 2024)
The relationship between physical activity and academic performance is a topic of interest in education and public health research. While the exact nature of this relationship can vary among individuals, there is evidence to suggest that regular engagement to physical activity can have a positive impact on academic performance. The main objective of this study was to determine the level of participation in physical activities and its relation to the academic performance of the CASE students of Colegio de la Purisima Concepcion. Specifically, the study was focused on finding answers to the following questions: 1) What is the socio-demographic profile of the respondents? 2) What is the level of participation in physical activities of the CASE students as a whole and in terms of sports and simple exercise? 3) What is the level of the academic performance of the CASE students? 4) Is there a significant difference in the level of participation in physical activities of the CASE students when grouped according to sex, year level, and program? 5) Is there a significant difference in the academic performance of the CASE students when groupedaccording to sex, year level, and program? and 6), Is there a significant relationship between the physical activity participation and the academic performance of the CASE students?The descriptive-correlation design was used in the study to determine the relationship between the level of participation in physical activities in terms of sports and simple exercises and the academic performance of the 130 students-respondents. A questionnaire, composed of three parts was used to gather data from the respondents which was validated by a panel of experts and was tested for reliability before it was distributed to the respondents. Prior to the distribution of the questionnaire, the researcher sought permission and approval to conduct the study from the dean of the CASE department. The data gathered were tabulated and analyzed using SPSS. Results revealed that considering the socio-demographic profile of the respondents, majority were females, first year level, and taking up Bachelor of Secondary Education program. As regards to the level of participation in physical activities of the respondents, the result was verbally interpreted as “high.” Results also disclosed that the students involve themselves in sports, and they participate in sports-related school activities. The result further highlighted that participation in physical activities like doing simple exercises, interest the students in a usual manner, They involve themselves in physical exercises the most to improve their mental health and academic performance as well. However, they do less of hard exercises. They prefer light type of exercises. Findings on the academic performance of the students as a whole, presented a grade point average of 1.79, interpreted as “very good,” indicating that students in the CASE department have a commendable academic performance in their preliminary grade. They exude excitement in the first few months of the school days. There was no significant difference in the level of participation of the students in physical activities when they were grouped according to sex, year level and programs. Likewise, there was no significant difference in the academic performance of the students in terms of prelim grade weighted average when they were grouped according to sex. However, a significant difference was noted in the year level and programs. Finally, no significant relationship was found between the level of physical activity participation and the academic performance of the students. This means that participation in physical activities has no bearing in the academic performance of the students.